Classification and properties of the structures of urbanized landscapes - Железняк, О.О. (Science-based technologies, 2018)
On the basis of data from the infrared space survey the classification and geospatial analysis of landscape structures of the big cities of Ukraine - Kyiv, Dnipro, Odessa, and Kharkiv has been carried out. The specifics of each of the cities and the ratio of the areas of territories occupied by each landscape structure - residential areas, structures of city transport systems, industrial formations, water landscape structures and recreational urban areas are determined. These landscape structures have their own physical and chemical properties (emissivity, albedo, roughness of the surface, relief, chemical composition). In this regard, they interact differently with solar radiation and have their own thermal spectrum of electromagnetic waves. It is established that in urbanized landscapes there are thermal anomalies of natural and anthropogenic origin. Urban development creates a change in the albedo and emissivity of the territory, which causes the process of formation of thermal islands. It is also established that the value of the gradient (temperature difference) between the territory of the specified cities and suburban areas greatly depends on the ratio of the area of ​​the recreational zones and the areas of industrial formations and residential areas. For Kharkiv it is 12-17 degrees, for Odessa - 10-12 degrees, the Dnieper - 14-16 degrees, Kiev - 8-10 degrees. These amplitudes of gradients have spatial and temporal properties (daily and seasonal cycles).